PENGARUH KINERJA KEUANGAN TERHADAP CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2018 - Denia Roswita Anisdhita; Hartaty Hadady; Johan Fahri (Jurnal Manajemen Sinergi, 2021)
ABSTRACTObjective: This study aims to determine the effect of financial performance on corporate social responsibility. The population in this study are banking companies listed on the Indonesia Stock Exchange (IDX) of 45 companies. Determination of the sample using purposive sampling. The samples used in this study were 21 companies with 105 observations. Methodology: The analytical model used to test hypotheses is multiple linear regression analysis and uses SPSS as a statistical test tool.Finding: H1, H2, and H3 Â accepted at the 5% confidence level.Conclusion: The results of this study indicate that company size (X1) has a negative and significant effect on corporate social responsibility. The bigger the size the company then the existence of assets owned by the company is unemployed, forcing the company to spend more costs, thereby reducing the allocation of costs used to disclose broader social information. Profitability (X2) has a positive and significant effect on corporate social responsibility. the greater the level of profits owned by the company, the wider the company discloses social information. While leverage (X3) does not affect corporate social responsibility. The higher or lower level ofleverage owned by a company will not influence the company in disclosing its social information.Â